Status Pencemaran Lingkungan Sungai Badung dan Sungai Mati di Provinsi Bali Berdasarkan Bioindikator Phylum Annelida - Labbaik, Mawardi; Restu, I Wayan; Pratiwi, Made Ayu (Journal of Marine and Aquatic Sciences; Vol 4 No 2 (2018)DO - 10.24843/jmas.2018.v4.i02.304-315, 2017)
Water pollution is the entry or inclusion of substances, energy and other components into the water by human activities, so that water quality decrease to a certain level. This study a timed to monitor the pollution of aquatic environment in the Badung River and Mati River by using Annelida phylum as bioindicator, the study was conducted from February to March 2017. The data obtained were analyzed by the structure of the community, and also used ABC ( Abudance-Biomass Comparison ) method. The result of the research showed that the most abundance of Annelida and dominant from all stations of Badung River and Mati River was Lumbriculus variegatus . Is showed that it contamination status was categorized as mild contamination because it was dominant by facultative organism. The structure of the Annelida community in the Badung River and Mati River with the value of the diversity index was categorized as low Annelida (H '<1.0). The uniformity index was categorized as depressed Annelida community (0.00 <E 0.50), high dominance index of Badung River (0.75 <C ? 1.00), Mati River was medium (0.50 < C < 0.75). The result of the water quality range as the supporting factor showed the average support for Annelida life i.e the current velocity 0.16 - 0.61 m/s, the temperature 25.5 - 31 o C, DO 3-7.2 mg/l, pH 7.77 - 8.44 and BOD 5 0.5 - 3.1 mg/l. The analysis environmental pollution condition of Badung River and Mati River with Annelida as bioindicator by using ABC method showed that were medium contaminated.